Чэнь Жиньмин “Шинэ Хятад улсаас гадаадад олгох зээл тусламжийн стратегийн судалгаа” номын тухай (Journal of International Studies, 2011)
English title: Critics on Cheung Jinmin's book “Strategic study on loans to be issued by New China, for foreign countries”